Reinvensi New Governance Bisnis Buah Mangga Berkelanjutan (Studi pada Ekonomi Buah Mangga Gedong di Jawa Barat, Indonesia) - Anang Muftiadi; Heru Ryanto; Teguh Santoso; Pandi Pardian; Adhadian Akbar; Mia Meliani (Jurnal Administrasi Bisnis, 2023)
Success and sustainability of business requires alignment of institutions and the ecosystem.  Aligment weaknesses in Gedong Mango fruit, from Sumedang, Jawa Barat coincide with export market prospect to Japan and high  value-added of processing .  Therefore a new governance framework is required. This study aims to calculate the value added in value chain using the Hayami Method and mapping power and interests of stakeholders. as foundation of new a governance system. The results show that the economy of Gedong  Mango Sumedang is evolutionarily disadvantageous for position and income of farmers, as indicated by un-even distribution of value-added in the supply chain and uncertainty of direction of change. The negative impact is that the prospect of  large market will not be able to increase and balancing income and welfare of farmers and other stakeholders. A new business governance  transformed by positioning the cooperative as a node of relationship and as driver, which is directed by a committee of stakeholder representatives with government facilitation.Keberhasilan dan keberlanjutan bisnis membutuhkan kelembagaan yang selaras dengan ekosistem. Kelemahan dalam hal tersebut dihadapi oleh produk buah Mangga Gedong dari Sumedang Jawa Barat, ketika prospek pasar ekspor ke Jepang dan nilai tambah hasil pengolahannya tinggi. Untuk itu, diperlukan suatu kerangka governance baru yang tepat. Penelitian ini bertujuan menghitung nilai tambah dan rantai nilai Mangga Gedong menggunakan Metode Hayami dan memetakan power dan interest para stakeholders menjadi suatu sistem governance. Hasil penelitian menunjukkan bahwa perkonomian Mangga Gedong Sumedang secara evolutif kurang menguntungkan posisi dan pendapatan petani yang ditunjukkan oleh ketidakseimbangan distribusi nilai tambah pada rantai pasok dan ketidakpastian arah perubahan. Dampak negatifnya, prospek pasar yang besar tidak akan dapat meningkatkan pendapatan dan kesejahteraan petani dan stakeholders lain secara seimbang. Karena itu diperlukan new business governance formdengan cara memposisikan koperasi sebagai simpul relasi dan driver yang diarahkan oleh komite para wakil stakeholders dengan fasilitasi pemerintah.